The deadliest fires then and now - Hopkinson, Deborah (Scholastic Focus, 2022)
"As the sun sank over the town of Peshtigo, Wisconsin, one warm October night in 1871, a smoky haze hung in the dry air. There had been little rain, and small fires had been rolling through town continuously since the summer. For weeks the people had tried to protect their homes and businesses from fire. But they could not protect themselves from what would culminate in the deadliest fire in American history. As industrialization surged across the country, and Westward colonization leveled forests to build cities, fires became a mainstay in American life. And as populations grew, so too did the human toll that fire could exact. Through the nineteenth and twentieth centuries, Americans searched for new and innovative ways to combat the threat of fire. And with climate change threatening to set the whole world aflame, we are once again in a fight for our planet's future. Through the eyes of scientists, witnesses, and survivors of terrible fires alike, Sibert Honor author Deborah Hopkinson brings the horrific history of deadly fires to life, tracing a line from the Peshtigo and Great Chicago fires of 1871 to the wildfires raging in the western United States today"--